Performance of cross glued laminated wood panels made of eucalyptus, rubber tree and bamboo (Research, Society and Development, 2021)
The aim of this research was to evaluate the physical and mechanical properties of cross-glued laminated wood (MLCC) and cross-glued laminated bamboo (BLCC) panels. For the bonding of veneers of wood (Eucalyptus grandis and Hevea brasiliensis) and bamboo (Dendrocalamus giganteus) an adhesive based on resorcinol-formaldehyde (RF) was used in ratio 350 g.cm-2 per double line of glue. The slides were cold pressed under a pressure of 1MPa at room temperature for a period of 24 hours. Three species-based treatments were adopted: 1) eucalyptus lamellae; 2) rubber tree coverslips; 3) Bamboo Coverslips. Bulk density, moisture content, water absorption, static bending modulus of elasticity (MOE) and modulus of rupture (MOR) parallel and perpendicular and shear strength in the glue line were evaluated. The results of the chemical analysis indicated a higher content of extractives and lignin for eucalyptus. Bamboo had the highest density, differing significantly from the others. The rubber tree MLCC panels showed lower moisture content and higher water absorption rate. For the parallel MOE property, the rubber tree MLCC panels showed a higher mean value while the perpendicular MOR of the bamboo panels showed a higher mean value. For shear strength in the glue line, all evaluated treatments met the normative requirements of EN-314-2:1993. Among the species analyzed, bamboo is recommended, which has shown great potential for the manufacture of MLCC, in addition to representing a sustainable option for the future.